Factors Influencing Adoption of Instructional Technologies by Faculty Members of the Mindoro State College of Agriculture and Technology - Mores, Ma. Concepcion L.; Zamora,; Jesse T. (JPAIR Multidisciplinary Research, 2010)
This paper investigates the level of instructional technology adoption by faculty members at Mindoro State College of Agriculture and Technology (MinSCAT) through empirical research. It identifies factors influencing their technology use. The study found that faculty members primarily used instructional technologies for class preparation and student activities only a few times a year. Even less frequent was technology use for classroom instruction, documenting and evaluating instruction, and professional email (once or twice a year). Interestingly, the level of adoption significantly correlated with age, gender, and tenure, but not with factors like civil status, education level, academic discipline, teaching experience, teaching load, academic rank, recent technology training, or holding an administrative position. However, faculty members’ perceived value of technology, self-efficacy in using it, and their perceptions of instructional resources, professional development opportunities, and college leadership all showed significant positive correlations with their technology adoption level. To improve technology adoption, the paper proposes the creation of an Instructional Technology Unit at MinSCAT. This unit would focus on activities like programming professional development workshops, building faculty core values regarding technology use, promoting equitable technology access, standardizing technology systems and procedures, developing equipment maintenance and repair programs, and expanding internet access.